Valor diagnóstico de las diferentes pruebas de laboratorio en la determinación de Plasmodium sp - Urdiales Vimos, Liseth Valeria (2022)
ABSTRACT Malaria is an infectious disease that causes a large number of deaths worldwide. The objective of this project was to deduce the diagnostic value of the different laboratory tests in the determination of Plasmodium sp. The present study was descriptive, with a documentary, non-experimental design and with a cross-sectional cohort. The population studied was made up of 100 bibliographic sources of which, after applying the inclusion and exclusion criteria, 50 were selected. The sources were selected from different repositories such as: Scielo, NCBI, Mediographic, Elsevier, Scopus, Google Scholar, Revista Eugenio Mirror, Synergy Magazine, MedCental Magazine, MSP, Journal, Link Springer. After carrying out this study, it is concluded that sociodemographic factors have a high influence in endemic areas because the majority of people infected by the infection belong to the rural population. The main signs and symptoms most frequent in this investigation appear after 10 to 15 days of having been infected by the mosquito, presenting symptoms such as: general malaise, headache, abdominal pain, chills and fever; The most used techniques to determine the diagnosis of Plasmodium are: peripheral blood smears, thick smears, immunology techniques such as rapid test tests (RDT), these detect antigens of the parasite found in the blood through immunochromatography and immunochromatography tests. PCR that allows detecting the four species of the parasite. Keywords: Plasmodium sp, malaria, Anopheles, thick film.